PENINGKATAN PEMAHAMAN LITERASI ANAK DAN REMAJA DI DESA SUKAREMA KECAMATAN LENEK - Munir, Muhammad Munir; Alwan, Muhammad Alwan; Husairi, Husairi; Lisnawati, Lisnawati; Nita, Nita Sunarya Herawati; Hayaturrayan, Hayaturrayan; Sholehah, Hijriati Sholehah (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2022)
The implementation of digital literacy training in the village of Sukarema has a very big influence on changes in people's habits, especially parents in controlling and supervising children when carrying out activities related to digital literacy. The implementation of PKM activities is carried out using the lecture method, aiming to provide understanding to parents that digital literacy is very necessary to help children digitally. We use practical methods to strengthen understanding of digital literacy. After the PKM implementation took place, the community (parents) could feel positively both the usefulness and benefits of digital literacy in finding information related to learning and other things. In addition, about 83.3% of the Sukarema villagers use digital for more than 4 hours per day. This shows that the progress of digital literacy is growing very fast. This proves that the implementation of digital literacy training can increase public or parents' understanding of digital literacy and can control and supervise children in using digital.